CHEMICAL COMPOSITION OF SEPIA ORIENTALIS AND LOLIGO VULGARIS - PANDIT, A R; MAGAR, N G (Fishery Technology, 2016)
The chemical constituents of Sepia orientalis and Loligo vulgaris weighing between 200-300g have been studied. It has been found that these species could be classed as high protein and jow fat food and that these are good sources of calcium, phos phorus, iron and moderate amounts of B-group vitamins.